Exploring Glaucoma: From Pathogenesis to Emerging Diagnostic and Management Strategies - Rajesh Kumar Goit (Journal of Ophthalmology)
Glaucoma is a leading cause of irreversible blindness globally, affecting millions of individuals. It encompasses a group of progressive optic neuropathies characterized by retinal ganglion cell loss and visual field deterioration, often associated with elevated intraocular pressure. Despite advances in understanding the disease, glaucoma management remains challenging due to its complex pathophysiology, heterogeneous presentations, and the need for lifelong treatment. Given the rapidly evolving nature of glaucoma research and its multidisciplinary scope, there is a compelling need for a comprehensive review that synthesizes the latest findings, highlights key advancements, and identifies areas requiring further investigation. This review aims to serve as a comprehensive resource for ophthalmologists, researchers, and healthcare providers by offering an overview of glaucoma classification, pathophysiology, risk factors, diagnostic tools, and management options.